Sensory Characterization of llama burger with sanky peel - Contreras-López, Eliana (2020)
The aim of this study was to perform a descriptive analysis to evaluate the sensory properties and color parameters in the llama burger with sanky peel powder. Sensorial characterization was performed using the static sensory analysis technique, quantitative descriptive analysis (QDA), which provides information on the intensities of the sensory properties at a specific point in time. The antioxidant capacity of the sanky peel was quantified (77,50 ± 0,98 µmol trolox equivalents/g dry weight), a panel of sensorial judges was trained, flavor, aroma, texture and appearance were evaluated, furthermore color, pH and microbiological parameters were evaluated. QDA revealed that the sanky peel powder in the llama burger improved the scores of the sensory properties: salty taste, sour taste, oregano flavor, firm appearance and general acceptability, however no significant difference among sensory properties evaluated (p> 0.05), being possible to use as a natural additive to meat products because the sanky peel is high antioxidant capacity.